2006
DOI: 10.1002/jmor.10504
|View full text |Cite
|
Sign up to set email alerts
|

Linking form and function of the fibrous joints in the skull: A new quantification scheme for cranial sutures using the extant fish Polypterus endlicherii

Abstract: The aim of this study is to connect specific sutural morphologies with the specific types of deformation they experience. To meet this goal, we quantified the morphologies of the interfrontal (IF), interparietal (IP), and frontoparietal (FP) sutures in the extant fish Polypterus endlicherii, and used our published measurements of in vivo deformation of these sutures during feeding to infer how suture morphology and function are connected. Specifically, we found that three relatively simple measures of cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…Specifically, we found that the IF suture in Polypterus is tensed, whereas the IP suture is compressed during feeding (23). The FP suture of Polypterus may experience tension or compression (23), which probably indicates shearing or bending (27). Based on these correlations between suture form and function, we assume the following: that fossil sutures that plot in the morphospace volume defined by the Polypterus IF suture measurements (pink) experienced tension; that sutures that lie in the Polypterus IP volume (blue) experienced compression; and that fossil suture morphologies that fall in the Polyperus FP volume (green) of the morphospace experienced more complex loading conditions that would have been manifested as a combination of tension and compression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, we found that the IF suture in Polypterus is tensed, whereas the IP suture is compressed during feeding (23). The FP suture of Polypterus may experience tension or compression (23), which probably indicates shearing or bending (27). Based on these correlations between suture form and function, we assume the following: that fossil sutures that plot in the morphospace volume defined by the Polypterus IF suture measurements (pink) experienced tension; that sutures that lie in the Polypterus IP volume (blue) experienced compression; and that fossil suture morphologies that fall in the Polyperus FP volume (green) of the morphospace experienced more complex loading conditions that would have been manifested as a combination of tension and compression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five metrics (27) were used to quantify the surface traces and cross-sectional morphologies of the interfrontal (IF), interparietal (IP), frontoparietal (FP), and nasofrontal (NF) sutures in Eusthenopteron, Acanthostega, and Phonerpeton: (i) interdigitation index: the length of the suture in cross-section divided by the distance between its ends (21); (ii) amount of overlap (ϭ beveling) in cross-section (19); (iii) size of the largest interdigitation in the suture's cross-section; (iv) bone thickness at the suture; and (v) the index of sinuousity: length of the suture on the surface of the skull divided by the distance between its ends (equals the index of interdigitation in ref. 28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gross observation of the skulls only allowed the surface (ectocranial) trace of the sutures to be examined, a common practice done in many comparative studies (e.g., van Heerden, 1972;Wang et al, 2006); however this may not always indicate the internal structure of the suture (Markey and Marshall, 2007). The internal structure of only a few skulls could be observed, either through serial sections or micro-CT (see below).…”
Section: Materials and Methods Gross Anatomical Observationsmentioning
confidence: 99%